Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Kelurahan Karang Pawitan Kab. Karawang - Miawati, Miawati; Rismayadi, Budi; Sumarni, Neni (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research has the purpose of finding out the organizational culture and work environment on employee performance so that they have good performance. They research type used is quantitative. They data collection technique used in this study. Using the distribution of questionnaires to Kelurahan Karang Pawitan Karawang employees. With the use of interviews and observations. The population used is only 30 all populations are sampled, this research uses multiple regression analysis methods, with the help of SPPS 25 software. From the research results it was found that the F count of 1.542 was greater that the F table value of 3.33 and the significant value off 0.232 which is greater than 0.05. this indicates that the research results acceted H₀. simultaneously Organizational culture and work environment have a positive but insignificant effect on employee performance in Kelurahan Karang Pawitan Karawang.